Relationship of Over-the-top (OTT) Communications and Traditional Telecommunications Services: the Case of Thailand - Monarat Jirakasem; Hitoshi Mitomo (International Telecommunications Society (ITS), 2019)
This paper focuses on the relationship between over-the-top (OTT) and traditional communications services. Many analysts have stated OTT communications services might soon replace other communication services; however, the empirical study of this assumption is scarce, especially in the case of Thailand. This study thus aims to investigate the actual effects of OTT communications services on traditional communications services and whether OTT communications services can substitute or complement traditional communications services. The data used in this paper were collected in 2019 and comprised 1,052 observations. After the Probit analysis, the results stated the relationship between the two services depends on tariff type: they are complementary under a flat rate plan but substitutable under a use-dependent scheme. With respect to messaging feature, OTTs and short message services (SMS) and multimedia messaging services (MMS) are independent. The results contribute to the field of telecommunications and provide evidence of the substitution and guidelines for telecommunications policy makers in Thailand. Regulators and mobile operators should encourage the flat rate plan. For economic reasons, the regulation similar to traditional telecommunications might not be suitable; however, regulation regarding other issues should be addressed in further study.
Keywords: 330; Over-the-top (OTT) communications services; substitution; mobile telephony; messaging; Thailand